2014
DOI: 10.3389/fpubh.2014.00058
|View full text |Cite
|
Sign up to set email alerts
|

Jump In! An Investigation of School Physical Activity Climate, and a Pilot Study Assessing the Acceptability and Feasibility of a Novel Tool to Increase Activity during Learning

Abstract: Physical activity (PA) benefits children’s physical and mental health and enhances academic performance. However, in many nations, PA time in school is decreasing under competing pressures for time during the school day. The present paper argues that PA should not be reduced or seen as incompatible with academic learning. Instead, the authors contend that it is critical to develop tools that incorporate PA into content learning during the school day. To facilitate the development of such tools, the authors con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 33 publications
2
48
0
5
Order By: Relevance
“…39 44 Supplementary File 1 46 and two in high school 35 47 ( Supplementary File 1). Intervention length ranged from one-off sessions [48][49][50][51][52] to three years 39 44 53 54 . Of studies providing physically active lessons on multiple occasions, total weekly intervention duration ranged from 10 minutes 55 to 180 minutes a day 56 .…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 44 Supplementary File 1 46 and two in high school 35 47 ( Supplementary File 1). Intervention length ranged from one-off sessions [48][49][50][51][52] to three years 39 44 53 54 . Of studies providing physically active lessons on multiple occasions, total weekly intervention duration ranged from 10 minutes 55 to 180 minutes a day 56 .…”
Section: Study Selectionmentioning
confidence: 99%
“…Sample sizes ranged from n=21 49 to n=2,493 53 , with a total of n=12,663 across all included studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Importantly, a recent two-year longitudinal study demonstrated that pupils who engaged in physically active lessons were four months ahead in maths and spelling than their peers who only engaged in traditional classroom learning (Mullender-Wijnsma et al 2016). To date, while some literature would argue that physically active lessons have not always led to enhanced academic outcomes (Graham et al 2014), no study has found a negative effect compared to traditional classroom learning (Watson et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados variaron desde la evaluación de la conducta del estudiante en la tarea hasta la valoración de los resultados académicos más orientados hacia el logro y conocimiento. Los resultados fueron mejorados significativamente tras las intervenciones (Donnelly et al, 2009, Mahar et al, 2006, sostenidos en comparación con el grupo control (Grieco et al, 2009) o no fueron diferentes al grupo control (Graham et al, 2014, Helgeson, 2013. Estos datos sugieren que el aprendizaje y la atención pueden mejorar tras episodios de clases físicamente activas, lo que está en consonancia con numerosos estudios previos que encontraron un aumento del aprendizaje tras el ejercicio (Barr-Anderson, Au-Young, Whitt-Glover, Glenn, y Yancey, 2011; Tomporowski et al, 2011).…”
Section: Evidencias Sobre Las Clases Físicamente Activas Y Resultadosunclassified
“…(Stewart, Dennison, Kohl, y Doyle, 2004), Move to Improve (Dunn, Venturanza, Walsh, y Nona, 2012), o Move for Thought (Skrade y Vazou, 2013) o las guías de Reed (2009) y de Pangrazi (2009). Por ejemplo, Graham et al (2014) propusieron el programa ¡Jump in! en el que diseñaron colchonetas de respuestas educativas para su uso en las clases de matemáticas.…”
Section: Introductionunclassified